Trenggalek Community Empowerement Model Base on Local Food Innovation - Tranggono, Didiek; Trisna, Andre Yusuf; Nuryananda, Praja Firdaus (Future Science, 2020)
Trenggalek is a regency that has abundant natural resources. Located in East Java, Trenggalek has agricultural, plantation, and fishery products. Unfortunately, some of its villages are categorized as underdeveloped villages (Desa Tertinggal). Tegaren village was once a village with IDT (Inpres Desa Tertinggal) status, which then often received assistance from the government. Whereas Winong village, a neighbor of Tegaren village, is also included in a developing village. Tasikmadu village, especially Watulimo Subdistrict, coastal area, is categorized as a developed village, but there are still many poor people. The research that we have done is the development of the ABCD (Asset-Based Community Development) model by Christopher Dureau which focuses on asset utilization. To determine the development of the ABCD method, this study used a mixed approach (mix method) with interview instruments, observation, and questionnaire distribution. This research will focus on developing and empowering communities in underdeveloped villages of Trenggalek Regency by focusing on local food innovation. The conclusion from this paper includes some reflections on the extent to which the concept of local food innovations. First must be there must be support from the government through both sustainable agriculture programs and food processing innovation. Second, to improve community capacity through systemic and controllable empowerment program. In the last, empowerment base on local food can help the capacity of the community to increase economic effect more widespread and sustainable change.